Solar Kage / Fariswan Atan - Atan, Fariswan (2020)
Photon Solar Sdn.Bhd. was established in early may 2020. Founded by Mr. Fariswan Atan and his team. The nature of this company business is focus on manufacturing services. The firm is formed links with Malaysian affiliates. The development of the firm was done stage by stage, the first stage was collected the ideas from all the members of the firm and sync it with this modern era to ensure the ideas is not out of trend and worth developing. The next stage is to put together a business plan, a good business plan will give a good business lifespan. Every successful business constantly review the sets of plans this is because to ensures that the company will meets what its needs. Third stage was to think about the profit that will produce from this business, observe which angle that will produce the profit. The next stage is start up the business. The teams was seeking for some investments, hiring some staff and managing accounts. This is the most challenging stage of all, because to start a new business from scratch will never be easy. The last stage is to dealt with increasing of customers and revenues. The competition from other companies also give a challenging experience in terms of pricing. Lastly, the teams was to find a way to increasing the profit volume of the company.